Investigating Teachers’ Efficacy Beliefs in Managing English for Specific Purposes (ESP) Classroom - Afrezah, Novela Nur; Priyana, Joko; Widyastuti, Puspa; Syahfutra, Wandy (Jurnal Pendidikan Progresif, 2024)
Investigating Teachers’ Efficacy Beliefs in Managing English for Specific Purposes (ESP) Classroom. Teachers must have high self-efficacy beliefs to provide teaching methods or strategies properly. Objective: This research aims to measure ESP teachers' efficacy beliefs and identify the effect of teachers’ efficacy on ESP teaching performances. Method: This study used mixed-method research as a research design. The subjects were teachers who have experience in teaching ESP. The teachers came from several vocational high schools and higher education institutions. The researcher used the purposive sampling technique to determine the sample of this research. The quantitative data were obtained through a questionnaire to 30 teachers from several vocational high schools in Riau, and the researcher invited five teachers to join an interview session. Furthermore, thematic analysis was used to analyze the data by familiarizing with the data, categorizing the data through coding, and then organizing those codes into themes reflecting the subjects’ responses. Based on the data obtained, all participants exhibited high and medium levels of self-efficacy. Five aspects were involved in the questionnaire: efficacy for English, efficacy for curriculum implementation, efficacy for instructional strategies, efficacy for classroom management, and efficacy for student engagement. Findings: Among these aspects, efficacy for instructional strategy was the highest. Teachers with high self-efficacy excel in classroom management, create motivating environments, and adapt their strategies to meet student needs, leading to better academic outcomes. Proficiency in English also plays a crucial role in effective ESP teaching.  High teacher self-efficacy boosts motivation to deliver effective lessons, even with limited preparation time. The research emphasizes the reciprocal relationship between teacher efficacy and student performance, showing that confident teachers foster better learning environments. Keywords: classroom management, ESP teacher’s self-efficacy, ESP. DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202476